Isolasi Asam Lemak dan Kadar Pigmen Rumput Laut Cokelat Sargassum crassifolium sebagai Sumber Antioksidan Alami: Isolation of Fatty Acid and Pigment Cntent of Sargassum crassifolium as A Source of Natural Antioxidant - Grace Sanger; Verly Dotulong; Lena Jeane Damongilala (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2022)
Sargassum is a marine product, source of bioaktive compound with many divers biological activity, especially as antioxidant and anticancer. The bioactive compound of Sargassum have been utilized as health product in many Industry such as, food, medicine and cosmetic. Fatty acids, (E)-11-octyloxacyclododec-10-en-2-one were isolated from ethyl acetic fraction of brown seaweed Sargassum crassifolium. The aim of the research is to isolate and purification the fatty acid compound and measure the pigmen content and antioxidant activity of S. crassifolium. The method of reasearc as followed; Sargassum extracted using methanol after that the extract partitioned with hexane and ethyl acetic and rinsed with methanol using Colomn Chromatography (CC). Ethyl acetic was purificated and isolated using CC and Thin Layer Chromatography (TLC) was using to monitored and observed the compounds. Isolate of pure compounds of etil acetic fraction of S. crassifolium (FEtSar) was elucidated by basic NMR spectroscopy, FTIR and ESMS and compared with previous literature. The extract, fractions and isolated compound were tested for their pigment content (carotenoid and fucoxanthin) and antioxidant activity using DPPH. The result of study shown, extract, fraction and pure compound of ethyl acetate fraction of S. crassifolium, (FEtSar), (E)-11-octyloxacyclododec-10-en-2-one revealed have antioxidant compound. Therefore S. crassifolium is potencial as a source of natural antioksidant and in future could be explored as health product.